Structuring Framework for Early Validation of Product Ideas - Asmar, Laban; Grigoryan, Khoren; Low, Cheng Yee; Roeltgen, Daniel; KÃ¼hn, Arno; Dumitrescu, Roman (International Journal of Integrated Engineering, 2020)
The advancing digitalization leads to new challenges in the development of new product ideas. The systems, which need to be developed, are becoming increasingly complex. As complexity rises, so does the slowness of organizations. In order to remain innovative and be able to react quickly to changes in the market, validation approaches offer great potential. An essential focus is the early, customer-centric and continuous validation of development artefacts. This is the only way to cope with shorter development cycles, and develop products that address a real need. To plan a validation, engineers need to have an idea about the possibilities within a validation. This paper presents a structuring framework for early validation of product ideas, which contains the three tools of Validation Map, Building Block Cards and Validation Canvas. The objective is to enable easier planning of validation experiments.